Análise de sensibilidade na criação de bovinos de corte no Estado do Pará - Silva, Diogo Claudio da (Universidade Federal do Tocantins, 2021)
Brazil and a major meat producer and exporter, has the largest commercial herd in the world with around 215 million head, while Pará is in the 4th position in number of cattle in the country, with 22 million head. In the country, 80% of the cattle are beef cattle, with breeding in all Brazilian municipalities, mostly calf production, many producers do not have the records of information on the cost of production and the viability of the business, the sensitivity analysis and an important instrument, and of total importance because it helps to know the results, profitability for decision making. Therefore, the objective of this was to make a sensitivity analysis, for this, a case study was done, where the zootechnical indexes, the support of the property were raised and a projection of the herd, during the period of 10 years, to find the recipe and verified the expenditures, both fixed and variable, and also investments in infrastructure to find property expenses in the period, the economic indexes were found and a sensitivity analysis was carried out on a rural property in Santa Maria das Barreiras, in the State of Pará. Concluding that project is robust and feasible, with attention to the expected profitability.